Stimulative Effects of Low Intensity He-Ne Laser Irradiation on the Proliferative Potential and Cell-Cycle Progression of Myoblasts in Culture - Cui-Ping Zhang; Shao-Dan Li; Yan Chen; Yan-Ming Jiang; Peng Chen; Chang-Zhen Wang; Xiao-Bing Fu; Hong-Xiang Kang; Ben-Jian Shen; Jie Liang (International Journal of Photoenergy)
Low intensity laser irradiation (LILI) was found to promote the regeneration of skeletal muscle in vivo but the cellular mechanisms are not fully understood. Myoblasts, normally quiescent and inactivated in adult skeletal muscle, are a type of myogenic progenitor cells and considered as the major candidates responsible for muscle regeneration. The aim of the present study was to study the effect of LILI on the growth potential and cell-cycle progression of the cultured myoblasts. Primary myoblasts isolated from rat hind legs were cultured in nutrient-deficient medium for 36 hours and then irradiated by helium-neon laser at a certain energy density. Immunohistochemical and flow cytometric analysis revealed that laser irradiation could increase the expression of cellular proliferation marker and the amount of cell subpopulations in the proliferative phase as compared with the nonirradiated control group. Meanwhile, the expressions of cell-cycle regulatory proteins in the laser-treated myoblasts were markedly upregulated as compared to the unirradiated cells, indicating that LILI could promote the reentry of quiescent myoblasts into the cell division cycle. These results suggest that LILI at certain fluences could promote their proliferation, thus contributing to the skeletal muscle regeneration following trauma and myopathic diseases.